The Impact of Self-Management Techniques to Improve University Students’ Social Cognition - Handayani, Mita Sri; Wangid, Muhammad Nur; Julius, Andre (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2021)
The background of the current study is the urgency of possessing good social cognition to adapt to the social changes that are happening quickly. Weak social cognition makes individuals less in empathy, aggressive or unhappy in their daily life. The link between self-management and social cognition lies in cognitive adjustment. Hence, the authors think it is important to do research that focuses on the implementation of counseling with self-management techniques in developing social cognition. The authors aimed to investigate the effectiveness of self-management in improving social cognition. The present study used one group pretest-posttest quasi-experiment. We invited 10 students from Universitas Ma'soem, Indonesia to participate in the experiment. They were selected based on a low social cognition score after filling the self-report of nineteen items social cognition scale. The results showed counseling with self-management techniques effective in improving university students' social cognition. Besides, limitations and recommendations are discussed.